An energy-based model to assess multiaxial fatigue damage under tension-torsion and tension-tension loadings. (December 2020) - Wei, Haoyang; Liu, Yongming
Highlights: A multiaxial fatigue criterion is proposed for arbitrary complicated loadings. The effect of hydrostatic energy is included in the proposed criterion. A loading transformation is proposed based on distortional and dilatational energy. The proposed model is validated under tension-tension and tension-torsion loadings. The influence of hydrostatic component in damage is discussed. Abstract: A new energy-based fatigue life prediction model is proposed for arbitrary multiaxial constant loadings in this paper. First, a brief review for existing multiaxial fatigue models is given, especially focusing on energy-based models. It is observed that most multiaxial model formulation and validation are suitable for axial-torsional loadings, but may not be appropriate for biaxial tension-tension loading. One possible reason is the ignorance of hydrostatic stress-state difference under these two types of loadings. In view of this, a new model is proposed by including fatigue damage contributions of equivalent tensile energy, torsional energy, and hydrostatic energy. Next, a loading transformation is proposed to transfer a complicated three-dimensional loading to an effective loading for life prediction. Detailed discussion of different types of multiaxial loading and its relationship with the ratio of distortional energy and dilatational energy is given. The hysteresis energy can be calculated integrating the proposed model with the Garud cyclic plastic model, which is directly linked to the damage accumulation and fatigue life prediction. The proposed model is validated with extensive experimental data under both tension-torsion loadings and biaxial tension-tension loadings from open literature. Comparison with several widely used multiaxial model is also given to show the model performance with respect to different biaxial tension-tension loadings. Finally, concluding remarks and future work based on the investigated materials are discussed.